Resource recovery from wastewater : a research agenda : WERF research report series - Burn, Stewart; Muster, T. H. (Timothy Harvey), 1973-; Kaksonen, Anna; Tjanatmadja, Grace (Water Environment Research Foundation ; IWA Publishing, 2014)
Traditionally wastewater treatment involved the removal of pollutants from wastewater to allow it to be discharged to the environment. This initially concentrated on carbon removal, but as environmental requirements became more stringent it was expanded to cover nitrogen and phosphorus removal. With increasing energy costs, more stringent environmental discharge limits and greater implementation of water sensitive urban design the economic viability of recovering water, energy and resources from wastewater is being considered more seriously. There are many examples worldwide of wastewater reuse and the methodologies are well known for the recovery of water which represents the most valuable resource in wastewater. On the contrary, the widespread application of energy, nitrogen and phosphorus recovery is just beginning to gain traction. A range of technological options for recovery of resources from wastewater are discussed in this report and in order of recovered value they include: 1) energy from methane capture, 2) direct phosphorus recovery, and 3) biosolids with improved phosphorus bioavailability. At this stage it is considered that the recovery of nitrogen via ammonia requires a step-change in technology for energy-efficient capture. Anaerobic wastewater treatment and more efficient anaerobic digestion of sludge offers major opportunities to improve the energy efficiency of the wastewater sector and to decrease biosolids levels, especially if additional sources of carbon can be included in the digestion process. However this raises the issue of the biologically un-available (refractory) carbon and how it can be converted to make it biologically available.